Some thoughts on the role of the Vietnamese state in the process of shifting to the market economy - Tran, Anh Tai (ĐHQGHN, 2017)
Nowadays, in the world, there are many different economic operation models at varying levels of success. Yet there is no model that operates without the State’s interference. A strong and intelligent state is one of the determinants for the success of an economic operation model.